Comparative analysis of university and high school students’ attitudes towards the idea of organ donation from deceased patients - Piwoński, Michał; Raksa, Karolina; Żak, Klaudia; Sidor, Katarzyna (Journal of Education, Health and Sport, 2019)
The transplantology is a branch of medicine, which has recently developed significantly. Nevertheless, despite a constant need for organs for transplantations, there is still no increase in supply for them. According to the Polish data, in 2018, only 629 new potential organ donors were registered in total and only 500 of them became so-called real donors. This data should provoque programmes to be created which would raise awareness of this problem. In the article, the results of the survey concerning university and high school students’ attitudes towards this issue were contained. As it turns out, not only young society’s attitude, but also its awareness of the organ transplantations should be taken care of.